Is cognitive reserve associated with cognitive function across stroke severity? A longitudinal study among Chinese stroke patients - Ou, Yinuo; Zhang, Yanrong; Lv, Yalin; Ding, Silian; Kong, Xiangjing; Xu, Hanzhang; Wu, Bei; Wei, Hui; Li, Juan (Frontiers in Aging Neuroscience, 2025)
BackgroundCognitive decline is common after stroke. This study assessed the longitudinal associations between cognitive reserve and post-stroke cognitive function and tested whether these associations differ across patients’ stroke severity.MethodsA longitudinal survey was conducted among 371 patients with acute ischemic stroke from four stroke centers in China from 2022 to 2023. Eligible patients were recruited at acute stage and followed up at 3 and 6 months after onset. Cognitive reserve was assessed by Cognitive Reserve Index questionnaire within 7 days after stroke onset. Cognitive function was assessed by Montreal Cognitive Assessment, Changsha Version at each time point. Stroke severity was assessed using the National Institutes of Health Stroke Scale at admission. Linear mixed models were applied to assess associations between cognitive reserve and cognitive function across stroke severity.ResultsAmong stroke survivors, cognitive function improved over time after the onset (βtime = 0.40, p<0.001). Higher level of cognitive reserve was associated with better cognitive function (βcognitive reserve = 0.08, p<0.001) after controlling for covariates. These associations remained over time (βcognitive reservetime = 0.01, p = 0.009) and did not differ across patients with different stroke severity (βcognitive reservestrokeseverity = 0.01, p = 0.11).ConclusionCognitive reserve can potentially mitigate the impact of stroke on long-term cognitive decline in Chinese patients with acute ischemic stroke. Targeting cognitive reserve may be a viable strategy to prevent or slow post-stroke cognitive decline. The study supports a more nuanced assessment of cognitive reserve as a standard in clinical studies.